Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the equation [tex]\( x = \lg \left(\frac{1}{3-2x}\right) \)[/tex], let's begin by understanding and transforming the given equation step-by-step.
### Step 1: Rewrite the Logarithmic Equation
The given equation is:
[tex]\[ x = \lg \left(\frac{1}{3-2x}\right) \][/tex]
We know that for any [tex]\( a > 0 \)[/tex] and [tex]\( a \neq 1 \)[/tex]:
[tex]\[ \lg \left(\frac{1}{a}\right) = -\lg(a) \][/tex]
So, applying this property to our equation:
[tex]\[ x = -\lg(3 - 2x) \][/tex]
### Step 2: Express in Terms of Logarithmic Equality
By rearranging, we can rewrite the equation as:
[tex]\[ x = -\lg(3 - 2x) \][/tex]
### Step 3: Introduce a Suitable Straight Line
Notice that [tex]\( y = \lg(a) \)[/tex] can be expressed as [tex]\( a = 10^y \)[/tex]. Trying to find a linear relationship, consider the transformation:
[tex]\[ y = \lg(3 - 2x) \Rightarrow 3 - 2x = 10^y \][/tex]
### Step 4: Formulate a Linear Equation
From the expression [tex]\( 3 - 2x = 10^y \)[/tex], let's isolate [tex]\( y \)[/tex]:
[tex]\[ y = -x \][/tex]
Thus, the equation of the suitable straight line becomes:
[tex]\[ y = -x \][/tex]
### Step 5: Compare with Another Function
We also need to consider the function [tex]\( y = \frac{1}{10^x} \)[/tex].
### Step 6: Intersection of Functions
To find the number of solutions, we look for the intersection points between [tex]\( y = -x \)[/tex] and [tex]\( y = \frac{1}{10^x} \)[/tex].
Equate the two equations:
[tex]\[ -x = \frac{1}{10^x} \][/tex]
### Step 7: Solve the Equation
Multiply both sides by [tex]\( 10^x \)[/tex] to clear the denominator:
[tex]\[ -x \cdot 10^x = 1 \][/tex]
### Step 8: Analyze the Equation
The function [tex]\( -x \cdot 10^x \)[/tex] is monotonic for [tex]\( x > 0 \)[/tex] (it decreases rapidly) and [tex]\( x < 0 \)[/tex] (it decreases rapidly as well). Therefore, examine the behavior only in the critical zones.
### Numerical or Graphical Solution:
This transcendental equation does not have a straightforward algebraic solution. Let's analyze it graphically or numerically.
Use the nature of the functions:
- [tex]\( y = -x \)[/tex] is a linear function.
- [tex]\( y = \frac{1}{10^x} \)[/tex] intersects with [tex]\( y = -x \)[/tex] at some [tex]\( x \)[/tex] value.
By numerical approximation, we consider solving the equation:
[tex]\[ -x \cdot 10^x = 1 \][/tex]
To find the number of solutions:
- Both [tex]\( y = \frac{1}{10^x} \)[/tex] and [tex]\( y = -x \)[/tex] will intersect exactly once, because [tex]\( \frac{1}{10^x} \to 0 \)[/tex] as [tex]\( x \to \infty \)[/tex] and [tex]\( y = -x \to \infty \)[/tex] as [tex]\( x \to -\infty \)[/tex].
Therefore, there is exactly one solution to the equation.
### Conclusion:
- Equation of the straight line: [tex]\( y = -x \)[/tex]
- Number of solutions: One
### Step 1: Rewrite the Logarithmic Equation
The given equation is:
[tex]\[ x = \lg \left(\frac{1}{3-2x}\right) \][/tex]
We know that for any [tex]\( a > 0 \)[/tex] and [tex]\( a \neq 1 \)[/tex]:
[tex]\[ \lg \left(\frac{1}{a}\right) = -\lg(a) \][/tex]
So, applying this property to our equation:
[tex]\[ x = -\lg(3 - 2x) \][/tex]
### Step 2: Express in Terms of Logarithmic Equality
By rearranging, we can rewrite the equation as:
[tex]\[ x = -\lg(3 - 2x) \][/tex]
### Step 3: Introduce a Suitable Straight Line
Notice that [tex]\( y = \lg(a) \)[/tex] can be expressed as [tex]\( a = 10^y \)[/tex]. Trying to find a linear relationship, consider the transformation:
[tex]\[ y = \lg(3 - 2x) \Rightarrow 3 - 2x = 10^y \][/tex]
### Step 4: Formulate a Linear Equation
From the expression [tex]\( 3 - 2x = 10^y \)[/tex], let's isolate [tex]\( y \)[/tex]:
[tex]\[ y = -x \][/tex]
Thus, the equation of the suitable straight line becomes:
[tex]\[ y = -x \][/tex]
### Step 5: Compare with Another Function
We also need to consider the function [tex]\( y = \frac{1}{10^x} \)[/tex].
### Step 6: Intersection of Functions
To find the number of solutions, we look for the intersection points between [tex]\( y = -x \)[/tex] and [tex]\( y = \frac{1}{10^x} \)[/tex].
Equate the two equations:
[tex]\[ -x = \frac{1}{10^x} \][/tex]
### Step 7: Solve the Equation
Multiply both sides by [tex]\( 10^x \)[/tex] to clear the denominator:
[tex]\[ -x \cdot 10^x = 1 \][/tex]
### Step 8: Analyze the Equation
The function [tex]\( -x \cdot 10^x \)[/tex] is monotonic for [tex]\( x > 0 \)[/tex] (it decreases rapidly) and [tex]\( x < 0 \)[/tex] (it decreases rapidly as well). Therefore, examine the behavior only in the critical zones.
### Numerical or Graphical Solution:
This transcendental equation does not have a straightforward algebraic solution. Let's analyze it graphically or numerically.
Use the nature of the functions:
- [tex]\( y = -x \)[/tex] is a linear function.
- [tex]\( y = \frac{1}{10^x} \)[/tex] intersects with [tex]\( y = -x \)[/tex] at some [tex]\( x \)[/tex] value.
By numerical approximation, we consider solving the equation:
[tex]\[ -x \cdot 10^x = 1 \][/tex]
To find the number of solutions:
- Both [tex]\( y = \frac{1}{10^x} \)[/tex] and [tex]\( y = -x \)[/tex] will intersect exactly once, because [tex]\( \frac{1}{10^x} \to 0 \)[/tex] as [tex]\( x \to \infty \)[/tex] and [tex]\( y = -x \to \infty \)[/tex] as [tex]\( x \to -\infty \)[/tex].
Therefore, there is exactly one solution to the equation.
### Conclusion:
- Equation of the straight line: [tex]\( y = -x \)[/tex]
- Number of solutions: One
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.